THE PERIODIC PATTERN OF DIATOM SEDIMENTATION AND GEOCHEMISTRY OF DIATOM OOZES IN LAKE BAIKAL - Gavshin V.M.; Bobrov V.A.; Khlystov O.M. (My University, 2001)
The Upper Pleistocene paleoclimatic records according to data of deep-water drilling in the Black Sea and Lake Baikal have been correlated. It has been shown that in both basins the two last interglacials were characterized by intense diatom sedimentation. It is stated that the appearance of diatom oozes in the sediments is related to an increased inflow of dissolved silica and nutrient salts. In oceans, this occurred during a rise of internal water, and on continents it was caused by surface runoff in the epochs of intense chemical weathering. The association of biogenic silica with uranium and organic matter (mainly humic acids) occurs not in Lake Baikal only but is also characteristic of upwelling zones, where sedimentation of humic acids and uranium is believed to occur at the water-bottom boundary. It has been found that the Baikal diatom sediments, already enriched in uranium in the superficial layer, further accumulate it immediately beneath the redox boundary. It has been demonstrated that the distribution of "clastophilic" elements in the column of the Upper Pleistocene Baikal sediments is a mirror image of distribution of biogenic silica as a thinner. Each event recognized in the oceanic paleoclimatic record in this time range is clearly pronounced in the sediment columns of the Akademichesky Ridge in Lake Baikal.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен